Engineering Multidefects on CexSi1−xO2−δ Nanocomposites for the Catalytic Ozonation Reaction. Issue 4 (11th November 2021) - Esmailpour, Ali Asghar; Horlyck, Jonathan; Kumar, Priyank; Tsounis, Constantine; Yun, Jimmy; Amal, Rose; Scott, Jason
Abstract: Herein, it is shown that by engineering defects on Ce x Si1− x O2− δ nanocomposites synthesized via flame spray pyrolysis, oxygen vacancies can be created with an increased density of trapped electrons, enhancing the formation of reactive oxygen species (ROSs) and hydroxyl radicals in an ozone‐filled environment. Spectroscopic analysis and density functional theory calculations indicate that two‐electron oxygen vacancies (OV 0 ) or peroxide species, and their degree of clustering, play a critical role in forming reactive radicals. It is also found that a higher Si content in the binary oxide imposes a high OV 0 ratio and, consequently, higher catalytic activity. Si inclusion in the nanocomposite appears to stabilize the surface oxygen vacancies as well as increase the reactive electron density at these sites. A mechanistic study on effective ROSs generated during catalytic ozonation reveals that the hydroxyl radical is the most effective ROS for organic degradation and is formed primarily through H2 O2 generation in the presence of the OV 0 . Examining the binary oxides offers insights on the contribution of oxygen vacancies and their state of charge to catalytic reactions, in this instance for the catalytic ozonation of organic compounds. Abstract : This work provides new insights into the contributions of different oxygen vacancy states in Ce x Si1− x O2− δ catalysts toward the activation of ozone/oxygen for the degradation of bisphenol‐A. Spectroscopic analyses and density‐functional theory calculations are used to demonstrate that two‐electron oxygen vacancies (OV 0, present as peroxide species) are more capable at this reaction than oxygen vacancies containing one and no electron.